Hubungan Iklan Rokok Dan Harga Rokok Terhadap Perilaku Merokok Pada Remaja Di Smk 1 Bengkulu Tengah - Arin Melinda; Darmawansyah Darmawansyah; Delta Aprianti (Utami Publisher, 2026)
An estimated 60 million Indonesians are active smokers. This contrasts with the decline in cigarette consumption in other countries. However, in Indonesia, the number of active smokers is predicted to increase to 150 million by 2025. The purpose of this reserach was to determine the correlation between cigarette advertising and cigarette prices on smoking behavior among adolescents at SMK 1 Bengkulu Tengah. The resesrach used a survey method with a quantitative approach. A sample of 61 students was selected using a purposive sampling technique. Univariate analysis was conducted to describe the frequency distribution of variables including cigarette advertising, cigarette price, and smoking behavior. Bivariate analysis, using the chi-square test, examined the relationship between cigarette advertising and smoking behavior, as well as cigarette price and smoking behavior. The results of the univariate analysis showed that 73.8% of respondents were exposed to cigarette advertising, 82% felt cigarette prices were influential, and 83.6% smoked. The bivariate analysis revealed a significant relationship between cigarette advertising exposure and smoking behavior (p = 0.001) and between cigarette price and smoking behavior (p = 0.001). Based on the research results, it is recommended that SMK 1 Bengkulu Tengah increase education and outreach regarding the dangers of smoking and collaborate with relevant parties to control cigarette advertising and set cigarette prices to reduce smoking interest among students.